Salesforce Process Builder Quick Start Guide : Build Complex Workflows by Clicking, Not Coding. - Gupta, Rakesh (Packt Publishing Ltd, 2018)
Salesforce Management System is an information system used in CRM to automate business processes like sales and marketing. Process Builder is a visual tool created to automate business processes in Salesforce. It enables users with no coding expertise to build complex Salesforce workflows.